Aplikasi Pembelian Tiket Pesawat: Memahami Determinan Niat untuk Melanjutkan Penggunaan - Selfira Salsabilla; Muamar Nur Kholid; Yestias Maharani (Faculty of Economic and Business, 2019)
Currently airplane passengers in Indonesia have a wide selection of airplane ticket purchase applications (PTP Application). The existence of various PTP applications in Indonesia makes it easy for users to stop using the PTP application and move to another PTP application. This study aims to identify the factors that influence the customer's intention to continue the use of PTP Application. This study uses the expectation confirmation model (ECM) by adding a trust variable. 203 respondents participated in this study. The model was tested using SmartPLS 2.0. The results of the study show that satisfaction is an important variable that influences the customer's intention to continue using PTP applications. In addition, trust and perceived usefulness have a significant positive effect on the intention to continue using PTP applications. Confirmation and usefulness perceptions have a significant positive effect on satisfaction and trust. This study discusses results of research both in relation to the theoretical and practical context.